On the boundary value problem π’β+π’=πΌπ’β»+π(π‘), π’(0)=0=π’(π)
On the boundary value problem π’β+π’=πΌπ’β»+π(π‘), π’(0)=0=π’(π)
In this note we consider the boundary value problem <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="u plus u equals a u Superscript minus Baseline plus p left-parenthesis t right-parenthesis comma u left-parenthesis 0 right-parenthesis equals 0 equals u left-parenthesis pi right-parenthesis comma alpha greater-than 0"> <mml:semantics> <mml:mrow> <mml:mi>u</mml:mi> <mml:mo>+</mml:mo> <mml:mi>u</mml:mi> <mml:mo>=</mml:mo> <mml:mi>a</mml:mi> β¦